The bush soldiers - Hooker, John, 1932- (London ; Sydney : Collins, 1984)
War time novel set in far western New South Wales, after the Japanese invade Australia ; includes Aboriginal characters.
Maps on lining papers.
Keywords: World War, 1939-1945 -- Fiction; Literature and stories - Non indigenous - Fiction; Defence - World War II; Murdi Paaki / Bourke (N NSW SH55-10); Broken Hill (NW NSW SH54-15)